Assessment of the AHRQ patient safety initiative : moving from research to practice evaluation report II (2003-2004) - Farley, Donna O.; Morton, Sally C.; Damberg, Cheryl; Ridgely, M. Susan; Fremont, Allen M.; Greenberg, Michael D.; Sorbero, Melony E. S.; Teleki, Stephanie S.; Mendel, Peter; Rand eBooks (Santa Monica, CA : RAND, 2007)
The Agency for Healthcare Research and Quality (AHRQ) is carrying out its congressional mandate to establish a patient-safety research and development initiative to help health care providers reduce medical errors and improve patient safety. In September 2003, AHRQ entered into a four-year contract with the RAND Corporation to serve as the Patient Safety Evaluation Center for its patient safety initiative. The evaluation center is responsible for performing a longitudinal evaluation of the full scope of AHRQ's patient safety activities and for providing regular feedback to support the continuing improvement of this initiative over the four-year project period. This report covers the period October 2003 through September 2004. It is the second of what will be four annual reports prepared by RAND during the formative evaluation. It builds on the preceding evaluation report, which covers the period October 2002 through September 2003. This report provides an update on the policy context that frames the AHRQ patient safety initiative, documents the evolution and current status of the priorities and activities being undertaken in the initiative, and lays out a framework and possible measures for evaluating the effects of the initiative on patient outcomes and stakeholders other than patients. Implications of the evaluation findings are discussed with respect to future AHRQ policy, programming, and research, and suggestions are presented for strengthening AHRQ activities as the initiative moves forward. The content and format of each report are designed to provide a stable structure for the longitudinal evaluation; the results of each year's assessment contribute to a cumulative record of the initiative's evolution. The contents of this report will be of interest to national and state policymakers, health care organizations and clinical practitioners, patient-advocacy organizations, health researchers, and others with responsibilities for ensuring that patients are not harmed by the health care they receive.
Introduction -- Context and input evaluations -- Process evaluation: monitoring progress and maintaining vigilance -- Process evaluation: patient safety epidemiology: effective practices and tools -- Process evaluation: building infrastructure for effective practices -- Process evaluation: achieving broader adoption of effective practices -- Product evaluation: selection of outcome measures -- Conclusion -- Appendix A: AHRQ-funded patient-safety-reporting demonstrations -- Appendix B: Summary of the AHRQ-funded challenge grants.
"RAND Health."
Cover title.
Includes bibliographical references (p. 75-77).
Also available on the internet via WWW in PDF format.
Keywords: Iatrogenic diseases -- Prevention -- Government policy -- United States; Medical errors -- Prevention -- Government policy -- United States; Patients -- United States -- Safety measures; Government Programs -- United States; Medical Errors -- prevention & control -- United States; Program Evaluation -- United States; Electronic books